Gas Chromatography-Mass Spectrometer Electron Ionization (GC-MS -EI)method for the Analysis of MalathionResidue in Tomato - Elbashir, Dr. AbdallaA; Ahmed, Hassan Elobid (JOURNAL OF ADVANCES IN CHEMISTRY, 2013)
In this a study tomato sampleswere collected from Khartoum, extracted with acetone, dichloromethane and petroleum ether (1:1:1) and cleaned up by florisil column. Malathion quantitative determination is carried out by gas chromatograph-mass spectrometerusing the optimum ionization mode electron ionization (EI). The detection ofmalathionis confirmed by retention time and comparison of primary and secondary ions.Recovery studiesÂ Â were performed at two spikes (0.5,0.25mg kg-1) fortification levels of malathion and the recovery obtained ranged from 81% to 97%. The method showed good linearity(RÂ²> 0.995) over the range assayed (from 0.05 to 7.0mg L-1) and the calculated limits of detection (LOD) and quantification(LOQ) were0.03 mg kg-1and 0.11 mg kg-1, respectively. These limitsÂ werelower than the maximum residue levels(MRL) established by European legislations (0.5mg kg-1).